INDUKSI KALUS TANAMAN KRISAN (Chrysanthemum morifolium) DENGAN PEMBERIAN BENZIL AMINO PURIN (BAP) DAN DICHLOROFENOKSI ACETIL ACID (2,4 D) - Maspan Hariyati; Imam Bachtiar; Prapti Sedijani (Postgraduate, University of Mataram, 2016)
Production of chrysant flowers (Chrysanthemum morifolium) is halted due to seedling supplay, that it is necessary to produce seedling on tissue culture. This study aims to determine the effect of BAP and 2.4 D for callus formation of chrysanthemum. The research using completely randomized design (CRD). The treatment was consistsed of two factors. BAP (0,0 mg/l, 1,0 mg/l, 1.5 mg/l and 2,0 mg/l) and concentration of 2,4 D (0,0 mg/l, 2,0 mg/l, 3,0 mg/l, 4,0 mg/l). Dependent variables measured were days of callus occurrence, callus colour and texture of callus. Result showed that growth regulators BAP and 2.4 D influenced the timing of the callus formation. Most rapid callus formation appeared at concentration of 2,0 mg/ l 2,4 D and longest callus formation appeared at concentrations of 0,0 mg/l 2,4 D. Callus did not appear on treatment of 0,0 mg/l BAP. The combination of BAP and 2.4 D did not influence on colour and texture of callus. Highest callus score was obtained in the treatment combination of D0B1, D0B0,5 and D0B2. The lowest callus score obtained in the treatment D4B0.Keyword: BAP, 2,4 D, Chrysanthemum morifolium, explants, Callus.